Acute Toxicity Test Of Guava Seed Ethanol Extract ( Syzygium Malaccense L ) Using The Brine Shrimp Lethality Test ( Bslt ) Method - Rahmadani Syafitri; Rosa Devitria (LPPM Universitas Abdurrab, 2024)
People generally treat infectious diseases using synthetic drugs that can have a n5egative impact. Therefore, one way to reduce the impact of synthetic drugs is to use medicinal plants. The meat, seeds, and leaves of Syzygium malaccense show the content of phenolic, flavonoid, and cartonoid compounds that are sources of antioxidant activity and have the opportunity to be used as medicinal plants. The aim of this study is to examine the potential for acute toxicity of Syzygium malaccense extract against the larval artemia salina leach using the BSLT (Brine Shrimp Lethality Test) method shown by the LC50 to ensure its safety if used by humans and to be the earliest stage for finding a new source of anti-cancer medicine. The extracts were made by maseration using a 96% ethanol solvent. The toxicity test was carried out using the 48-hour-old Artemia salina leach shrimp larva. The results of this study were analysed using the LC50 probit table for a 96% ethanol extract of rose bol seeds, which is 46,18 ppm. This suggests that the extract is highly toxic to Artemia salina leach.